Rekultywacja gleb leśnych zdegradowanych przez wypływ solanki w okolicach Głogowa = Reclamation of the forest soils damaged in result of salt mine-waters overflow in Głogów region - Greinert, Andrzej; Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In result of uncontrolled outflow of salty mine waters from pipelines it transporting follows the degradation, and even the devastation of soils. These situations are subject, with power of law, of the soils reclamation - the row of workings restoring them the functionality. The granulometric compound of soils cause diversification of reclamation techniques. The situation of salted clay soils reclamation has been described in article. In the paper has been showed the possibility of in-situ reclamation technique use. The main necessities are efficient meliorative net and in case of dry periods the possibility of area irrigation.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zasolenie; gleby leśne; skażenie gleb; detoksykacja gleb